2021
DOI: 10.1177/17590914211016217
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Parkinson’s Disease: Implications for Faecal Microbiota Transplantation Therapy

Abstract: Parkinson's disease (PD) ranks the second place among neurodegenerative diseases in terms of its morbidity, which affects 1-2% people aged over 65 years. In addition to genetics, some environmental factors may exert vital parts in PD occurrence as well. At present, more and more studies are conducted to elucidate the association between gut microbial dysbiosis and the incidence of PD. Gut microbial dysbiosis has a certain effect on both the central nervous system (CNS) and the enteric nervous system (ENS), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Since 2014, several large-scale case-control studies have shown significant changes in the gut microbiota composition [ 58 ]. In all of these studies, it was very problematic to establish the composition changes at the phylum level due to the high variability in the relative abundances of bacteria phyla in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2014, several large-scale case-control studies have shown significant changes in the gut microbiota composition [ 58 ]. In all of these studies, it was very problematic to establish the composition changes at the phylum level due to the high variability in the relative abundances of bacteria phyla in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are live microorganisms, which benefit the host if they are given in sufficient doses [50]; for instance, they improve gut microbial balance and stimulate bacte-rial products and metabolites [51]. The popularity of probiotics has expanded exponentially recently, due to their health promoting effects and their abilities to prevent or treat different diseases [52][53][54][55][56][57][58][59][60][61]. Likewise, many studies suggest that probiotics are effective on the treatment of liver diseases in animal models and human beings.…”
Section: Probioticsmentioning
confidence: 99%
“…FMT is a process that administers fecal matter solution obtained from a normal donor to the recipient intestinal tract, so as to directly change the microbial composition of the latter and induce the health benefits or treat a certain disorder [53, 54]. Since FMT has successfully been utilized among cases suffering from C. difficile infection, which can restore eubiosis and achieve better clinical improvements than those of standard antibiotic therapy, FMT is currently being assessed in some clinical studies to treat numerous other disorders, such as irritable bowel syndrome, inflammatory bowel disease, cardiovascular disease, and metabolic diseases [53, 54, 58, 66]. Recently, FMT has been shown to have a role in some types of cancer, such as non-small cell lung cancer, colorectal cancer, and melanoma [59, 67].…”
Section: Targeting Microbiota For Hcc Preventionmentioning
confidence: 99%
“…More detailed studies with due consideration given to other variables and also confounders are required at the moment. There is also a need to explore the exact mechanism by which FMT restores eubiosis and the exact changes in the gastrointestinal microbiota before and after FMT [38,39]. Only then can we move toward developing a standardized protocol for FMT.…”
Section: Role Of Fecal Microbiota Transplant In Restoring Eubiosismentioning
confidence: 99%
“…Kang et al [39] Traditional review To evaluate the latest available research on PD and its association with the gut microbiome, and to explore FMT as a future potential therapy.…”
Section: Lorente-mentioning
confidence: 99%